Pengaruh Edukasi Gizi terhadap Pengetahuan dan Sikap Konsumsi Sayur pada Anak Sekolah Dasar - Natasha, Nadya; Uswah, Jenny; Pertiwi, Lisa (Lembaga Publikasi Ilmiah Nusantara, 2025)
Vegetable consumption among elementary school children remains relatively low, although vegetables are an important source of vitamins, minerals, and fiber that play a vital role in children’s growth and development. Low vegetable intake is often influenced by a lack of nutritional knowledge and negative attitudes toward healthy foods. This study aims to analyze the effect of nutrition education on knowledge and attitudes toward vegetable consumption among elementary school students. This research employed a quasi-experimental design with a pretest-posttest control group approach. The subjects were elementary school students aged 9–11 years selected through purposive sampling. The intervention was conducted through nutrition education using interactive counseling, posters, and educational games over four weeks. Data on knowledge and attitudes were collected using standardized questionnaires, then analyzed using paired t-tests and independent t-tests to examine differences before and after the intervention between the experimental and control groups. The results showed a significant improvement in nutritional knowledge (p<0.05) and more positive attitudes toward vegetable consumption in the experimental group compared to the control group. Nutrition education proved effective in increasing students’ awareness of the importance of vegetable consumption and shaping more supportive attitudes toward healthy eating patterns. This study recommends that nutrition education programs be integrated into school activities as a promotive and preventive effort to establish healthy eating habits from an early age.